2020
DOI: 10.48550/arxiv.2008.05031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covert Transmission Assisted by Intelligent Reflecting Surface

Abstract: Covert transmission is studied for an intelligent reflecting surface (IRS) aided communication system, where Alice aims to transmit messages to Bob without being detected by the warden Willie.Specifically, an IRS is used to increase the data rate at Bob under a covert constraint. For the considered model, when Alice is equipped with a single antenna, the transmission power at Alice and phase shifts at the IRS are jointly optimized to maximize the covert transmission rate with either instantaneous or partial ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…1) Reflection Amplitude Optimization: Different from the above positive results of using IRS in covert communications, the work in [11] showed that IRS may be harmful to covert transmissions in some cases, even when the partial or full CSI of Willie's links is available.…”
Section: B Existing Challenges and Future Workmentioning
confidence: 99%
“…1) Reflection Amplitude Optimization: Different from the above positive results of using IRS in covert communications, the work in [11] showed that IRS may be harmful to covert transmissions in some cases, even when the partial or full CSI of Willie's links is available.…”
Section: B Existing Challenges and Future Workmentioning
confidence: 99%
“…With the help of IRS, [12] showed that covert communication performance can be improved in the single-input-single-output (SISO) system. The work of [12] was then extended to a more general system setup with both single antenna and multiple antennas at the legitimate transmitter in [13], and authors studied the IRSassisted covert communication under the assumption of infinite number of channel uses. In [14] authors considered the delayconstrained IRS assisted covert communication.…”
Section: Introductionmentioning
confidence: 99%